Mandau Syrup Production Factors in Kelayan A Banjarmasin - Hasanah, Hasanahh; Ilhami, M. Ridha; Sari, Raihanah; Rahmia, Sovia Husni; Triyono, Sigit (Program Studi Pendidikan IPS, 2026)
Mandau Syrup is a traditional beverage product unique to Banjarmasin that is still produced today using traditional methods in Kelayan A. This business is interesting to study because it has managed to maintain its existence amid the rapid development of the modern beverage industry, which is dominated by manufactured products. This study focuses on how production factors are utilized in the Mandau Syrup business in Kelayan A, Banjarmasin. This study aims to analyze the role of production factors, including raw materials, labor, capital, and entrepreneurship in the production of Mandau syrup. The research method used is descriptive qualitative with data collection techniques through direct observation, in-depth interviews with owners and workers, and documentation. The results show that Mandau syrup production is supported by easily obtainable raw materials such as sugar, food coloring, and flavorings from traditional markets; a workforce of four people relying on work experience; business capital of thirty million rupiah from personal funds without assistance from other parties; and entrepreneurship that emphasizes product quality consistency. These findings indicate that simple management of production factors remains effective in maintaining the sustainability of a business from generation to generation.